Strengths and opportunities to clinical trial enrollment among BIPOC, rural dwelling patients in the northwest United States: a retrospective study - Nelson, Jamie M.; Johnson, Elizabeth; Kiesow, Becky; McCrory, Bernadette; Ma, Jiahui (Frontiers in Pharmacology, 2024)
Introduction: Clinical trials investigating the safety and efficacy of experimental drugs and devices are the cornerstone of medicinal advancement. Enrolling sufficient participants in these trials is vital to ensure adequate statistical power and generalizability. Clinical trial participation is particularly low among certain populations, including medically underserved communities (i.e., rural areas) and Black, Indigenous, and People of Color (BIPOC).A retrospective study design was used to understand patient outcomes and access/barriers to clinical trial participation in the rural northwest United States. A quantitatively focused retrospective chart review was conducted for adult participants enrolled in at least one clinical trial in a single northwest health system between 1999 and 2022. Descriptive and inferential statistical analyses were performed to assess trial outcomes at a significance level 0.05.The retrospective chart review yielded 833 clinical trial records with 753 individual enrolled participants. The Aall-cause mortality relative frequency of death at last known follow-up amongst clinical trial participants was 8.90% (n=67). Based on logistic regression, the mortality death was significantly associated with the participants' age at initial trial screening (β = 0.09, P-value < 0.001), those that resided in non-metro areas (β = -0.86, P-value = 0.045), and those that lived in Northeastern Montana (β = 1.27, P-value = 0.025). Additionally, mortality death at last known follow-up was significantly associated with enrollment in 2021-2022 (β = -1.52, P-value < 0.001), enrolled in more than one study (β = 0.84, P-value = 0.023), in internationally sponsored trials (β = -2.08, P-value < 0.001), in Phase I (β = 5.34, P-value < 0.001), in Phase II trials (β = 1.37, P-value = 0.013), diabetes as a primary trial target (β = -2.04, P-value = 0.003).